The Possession Witchboard III - Peter Svatek; Addison, Bell.; Cedric Smith; Danette Mackay; Donna Sarrasin; Elizabeth Lambert; Richard Zeman; David Nerman (USA Vista Street Entertainment, 1995)
Brian, an out-of-work stockbroker, is introduced by his landlord Mr. Redman to a new source of insider information: the Ouija! The Ouija makes him rich, but when Mr. Redman kills himself and Brian suffers a freak accident, Brian's wife starts noticing changes in her husband...
A woman must battle for her loved one's soul when an ancient Ouija board opens a pathway to a demonic force
Jon Ezrine
Languages: English Subtitles: No Subtitles
Keywords: Horror